Super sniffers : dog detectives on the job - Patent, Dorothy Hinshaw (Bloomsbury, 2014)
"A dog's nose is 300 times more powerful than a human nose, so it's no wonder that dogs use their incredibly advanced sense of smell to do some very important jobs. Dorothy Hinshaw Patent explores the various ways specific dogs have put their super sniffing ability to use: from bedbug sniffers to explosive detectors to life-saving allergy detectors...and more. This dynamic photo-essay includes first-hand accounts from the people who work closely with these amazing dogs."--